The Future of Marine Biogeochemistry, Ecosystems, and Societies: IMBER IMBIZO III, Goa, India; 28–31 January 2013. (14th May 2013) - Bundy, Alida; Liu, Kon‐Kee; Thomas, Helmuth
Abstract : The international project Integrated Marine Biogeochemistry and Ecosystem Research (IMBER) convenes an IMBIZO (a Zulu word meaning "a gathering") biennially, with a format of three concurrent, interacting workshops designed to synthesize information on topical research areas in marine science. IMBIZO III, held at the National Institute of Oceanography in Goa, India, focused on multidimensional approaches to challenges of global change in continental margins (CM), open ocean systems, and dependent human societies. More than 120 participants from 29 nations attended the meeting; the smaller workshop groups allowed in‐depth discussions, and daily plenary sessions facilitated discussion among interdisciplinary experts.